Criminal Law Protection Of Giving Rights Of Liability Is Not The Debtor - Euis Listianti; Umar Ma'ruf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
In the practice of the loan agreement with collateral Mortgage made by banks as creditors, so if the debtor defaults in performing its debt to the creditor, the creditor has the right to make the execution of security object Encumbrance with its own power after first obtaining fiat yustitsia of the chairman of the court country where the land is located. In case of dispute the auction execution of mortgage security object between the Bank as the creditor with Zn as the debtor, as creditors of the bank's declared to have violated provisions of the law in the execution of security object security rights belonging to the debtor Zn. But in fact the execution and the execution of the auction object of mortgage collateral is in accordance with the provisions of Article 6 and Article 20 UUHT No. 4 of 1996 and also in accordance with the provisions and procedures of the auction procedure execution security object security rights under the laws of the auction. The problems addressed in this study is how to legality and legal power auction object execution Mortgage guarantees made at the request of creditors certificate holder.Keywords: Legal Protection, Criminal, and Encumbrance .